1999
DOI: 10.1680/macr.1999.51.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ground granulated blastfurnace slag on the sulphate resistance of lime-stabilized kaolinite

Abstract: This paper describes the influence of ground granulated blastfurnace slag (GGBS) on the durability of lime-stabilized kaolinite in 4·2% Na2SO4 solution. Sulphate durability was assessed in the laboratory by means of linear expansions measurements, microstructure and mineral phase analysis of compacted cylinders of the lime-stabilized kaolinite with different percentages of lime replacement by GGBS. The cylinders were immersed in 4·2% Na2SO4 solution and also in deionized water for various time periods. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Figure 3 shows the stress strain characteristics of soil sample 1 treated with GGBS. It can be observed that, a steady rise in the peak zone of a curve with 60 days curing as the UCS value increased to 1725kPa.This is found to be in agreement with the reported data in literature [20] that slag replacement increased Kimmeridge Clay strength to a maximum at 28 to 60 days curing. Thus, the gradual failure of samples highlights the brittle nature of GGBS treated soil.…”
Section: Influencial Behaviour Of Ggbs and Gsa On Compressive Stresupporting
confidence: 93%
“…Figure 3 shows the stress strain characteristics of soil sample 1 treated with GGBS. It can be observed that, a steady rise in the peak zone of a curve with 60 days curing as the UCS value increased to 1725kPa.This is found to be in agreement with the reported data in literature [20] that slag replacement increased Kimmeridge Clay strength to a maximum at 28 to 60 days curing. Thus, the gradual failure of samples highlights the brittle nature of GGBS treated soil.…”
Section: Influencial Behaviour Of Ggbs and Gsa On Compressive Stresupporting
confidence: 93%
“…The optimu m content of lime depends primarily on the type of soil and curing conditions [19].Previous engineering test results by other researchers have found that the optimu m lime-GGBFS rat io to achieve maximu m UCS is 1: 5 [ 17]. It was also suggested that this ratio o f a lime-GGBFS mixtu re is enough to activate GGBFS [45]. As shown in Figure 6, maximu m USC value is obtained in the sample which contains of 3% lime and 15% GGBFS.…”
Section: Unconfined Compressive Strength (Ucs) Testmentioning
confidence: 99%
“…So b lends of lime and GGBFS might be resistant to swelling caused by sulphate [44]. In addition, laboratory tests have shown a previously undemonstrated advantage where the incorporation of GGBFS co mbats the deleterious swelling which can occur when sulphate-containing soils are stabilised with cement or lime [45]. Higgins [19] showed that GGBFS was completely successful in reducing swelling caused by sulphate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Wild and co-workers in a series of publications [9][10][11][12][13][14][15][16] showed that replacing a part of the lime by BFS in stabilization of a kaolinite greatly reduced expansion both for internal and external sources of sulfate. They also developed a hypothesis based on the gel theory of expansion.…”
Section: Introductionmentioning
confidence: 99%